2002
DOI: 10.1590/s0102-44502002000200006
|View full text |Cite
|
Sign up to set email alerts
|

A evolução da noção de parâmetros

Abstract: This paper presents an overview of the concept of parameter in the* Agradeço a Ruth Lopes pela leitura cuidadosa da primeira versão deste trabalho e as sugestões pertinentes incorporadas nesta versão. Meus agradecimentos também a Maria Eugenia L.Duarte e Sonia Cyrino pela ajuda na localização de exemplos e referências.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
4

Year Published

2015
2015
2018
2018

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 32 publications
(10 citation statements)
references
References 6 publications
0
6
0
4
Order By: Relevance
“…Processing studies investigating functional morphology have shown that non-native speakers are not always sensitive to agreement violations (BOND et al, 2010;JIANG, 2007;SAGARRA;HERSCHENSOHN, 2011). If learners are insensitive to verbal inflectional morphology, we could hypothesize that they will have difficulty acquiring the feature bundle of Vocabulary items that instantiate verbal inflection.…”
Section: Discussionmentioning
confidence: 96%
See 4 more Smart Citations
“…Processing studies investigating functional morphology have shown that non-native speakers are not always sensitive to agreement violations (BOND et al, 2010;JIANG, 2007;SAGARRA;HERSCHENSOHN, 2011). If learners are insensitive to verbal inflectional morphology, we could hypothesize that they will have difficulty acquiring the feature bundle of Vocabulary items that instantiate verbal inflection.…”
Section: Discussionmentioning
confidence: 96%
“…In other words, a delay in reading ungrammatical sentences shows that the learner is sensitive to grammatical errors, which suggests that the activation of the related linguistic knowledge is automatic. Therefore, one can hypothesize that such linguistic knowledge has become integrated and automatized (JIANG, 2007).…”
Section: Morphological Sensitivitymentioning
confidence: 99%
See 3 more Smart Citations